Watch out where you sleep: nocturnal sleeping behaviour of Bay Island lizards - Nitya Prakash Mohanty; Surendran Harikrishnan; Karthikeyan Vasudevan (PeerJ, 2016)
Sleeping exposes lizards to predation. Therefore, sleeping strategies must be directed towards avoiding predation and might vary among syntopic species. We studied sleeping site characteristics of two syntopic, congeneric lizards—the Bay Island forest lizard, Coryphophylax subcristatus and the short-tailed Bay Island lizard, C. brevicaudus and evaluated inter-specific differences. We measured structural, microclimatic and potential predator avoidance at the sleeping perches of 386 C. subcristatus and 185 C. brevicaudus. Contrary to our expectation, we found similar perch use in both species. The lizards appeared to use narrow girth perch plants and accessed perches by moving both vertically and horizontally. Most lizards slept on leaves, with their heads directed towards the potential path of a predator approaching from the plant base. There was no inter-specific competition in the choices of sleeping perches. These choices indicate an anti-predator strategy involving both tactile and visual cues. This study provides insight into a rarely studied behaviour in reptiles and its adaptive significance.